Implementasi Penerapan Etika Bisnis Pemasaran Internet Wifi di PT Telkom Indonesia - Agung Joko Purnomo; A’rasy Fahrullah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Currently the internet service industry is very much sought after by the public, which focuses on the daily needs of consumers which causes the level of competition between companies to be high. Therefore, companies must increase brand capital and good service quality by means of effective marketing activities. This study aims to analyze how influential a marketing strategy in accordance with Islamic business ethics can create consumer interest in making customer satisfaction when making transactions, the method used in this study is a qualitative method which aims to explain the reality in the field, for the research subject technique uses purposive techniques. sampling where the researcher determines the sample to be interviewed based on who can represent a population, while the results of this study aim for the chosen marketing strategy to be a guideline that is in accordance with Islamic ethics to foster a sense of politeness, good and trustworthy delivery like the nature of the prophet, namely shidiq (true), amanah (trusted), tabliqh (deliver), fathonah (intelligent). Which is summarized in one SOE guideline, namely prioritizing morals in work and good service to all consumers